Assessing risk and guidance on monitoring of Batrachochytrium dendrobatidis in Europe through identification of taxonomic selectivity of infection - Baláž, Vojtech; Vörös, Judit; Civiš, Petr; Vojar, Jiri; Hettyey, Attila; Sós, Endre; Dankovics, Róbert; Jehle, Robert; Christiansen, Ditte G; Clare, Frances; Fisher, Matthew C; Garner, Trenton W J; et al. (Conservation biology, 2014)
Amphibians are globally threatened, but not all species are affected equally by different threatening processes. This is true for the threat posed by the chytridiomycete fungus (Batrachochytrium dendrobatidis). We compiled a European data set for B. dendrobatidis to analyze the trends of infection in European amphibians. The risk of infection was not randomly distributed geographically or taxonomically across Europe. Within countries with different prevalence, infection was nonrandom in certain amphibian taxa. Brown frogs of the genus Rana were unlikely to be infected, whereas frogs in the families Alytidae and Bombinatoridae were significantly more likely to be infected than predicted by chance. Frogs in the 2 families susceptible to B. dendrobatidis should form the core of attempts to develop spatial surveillance studies of chytridiomycosis in Europe. Ideally, surveys for B. dendrobatidis should be augmented by sampling the widespread genus Pelophylax because this taxon exhibits geographically inconsistent overinfection with B. dendrobatidis and surveillance of it may facilitate recognition of factors causing spatial variability of infection intensity. Several European amphibian taxa were not represented in our data set; however, surveillance of unsampled species should also occur when warranted.
Keywords: Prevalence; Chytridiomycota; Europe; Conservation of Natural Resources; polymerázová řetězová reakce; Polymerase Chain Reaction; disease; Evropa; Risk Assessment; prevalence; epidemiology; amphibians < animals; Amphibians; risk assessment; zachování přírodních zdrojů; mykózy; zvířata; hodnocení rizik; Mycoses; inventory and monitoring; conservation planning; obojživelníci; Animals